2018
DOI: 10.1007/s11270-018-3851-9
|View full text |Cite
|
Sign up to set email alerts
|

Brassica napus Growth in Lead-Polluted Soil: Bioaccumulation in Plant Organs at Different Ontogenetic Stages and Lead Fractionation in Soil

Abstract: Lead is known to be a highly toxic metal; it is often found in soils with the potential to be incorporated by plants. Here, the bioaccumulation of lead by rapeseed (Brassica napus) from a soil with Pb(II) added just before sowing is studied. The effect on plant organs is also studied at the ontogenetic stages of flowering and physiological maturity. Moreover, the chemical fractionation of Pb in the rhizosphere and bulk soil portions is investigated and related to Pb accumulation in plant organs. B. napus are f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Some tolerant plants tend to restrict soil-root and root-shoot transfers, and therefore accumulate low amounts of metals, while hyperaccumulators actively take up and translocate metals into their aboveground organs. Plants with TF and particularly BCF values below one are unsuitable for phytoextraction but may be efficient in phytostabilization schemes (Yoon et al 2006;Ferreyroa et al 2018). Our experiments with S. vulgaris calamine population showed that both Zn and Cd TF coefficients were too low to use this species for effective phytoextraction.…”
Section: Remediation Potential Of Calamine Ecotype Of Silene Vulgarismentioning
confidence: 79%
“…Some tolerant plants tend to restrict soil-root and root-shoot transfers, and therefore accumulate low amounts of metals, while hyperaccumulators actively take up and translocate metals into their aboveground organs. Plants with TF and particularly BCF values below one are unsuitable for phytoextraction but may be efficient in phytostabilization schemes (Yoon et al 2006;Ferreyroa et al 2018). Our experiments with S. vulgaris calamine population showed that both Zn and Cd TF coefficients were too low to use this species for effective phytoextraction.…”
Section: Remediation Potential Of Calamine Ecotype Of Silene Vulgarismentioning
confidence: 79%
“…Therefore, even the highest concentration measured in Brassica napus shoots was 26 times lower than in the sediment. Other authors also recorded low Pb uptake by Brassica napus [ 59 , 60 , 61 , 62 ].…”
Section: Resultsmentioning
confidence: 97%
“…Phytoextraction, the most common form of phytoremediation, uses hyper-accumulators able to extract 50-500 times more pollutants than normal plants, and genetic engineering has allowed to transfer hyper-accumulator genes from plants having low biomass to others with high biomass such as Brassica species [161]. Several Brassica species were reported to moderately accumulate quantities Cd, Pb, and As [167][168][169]. Furthermore, the use of chelating agents such as synthetic ethylenediaminetetraacetic acid, increasing the solubility of the metals in soils, improves plant metal uptake and, consequently, soil decontamination [161,164].…”
Section: Interventions Towards Mitigation Of Toxic Metal Effectsmentioning
confidence: 99%